Chinese investment in Greenland’s mining industry : toward a new framework for foreign direct investment. - Lasserre, Frédéric; Têtu, Pierre-Louis (The Extractive Industries and Society, 2017)
This paper examines the dynamics of Chinese investment in Greenland’s mining industry, drawing on findings from interviews with representatives from selected companies, organizations, and financial institutions. Support from the central government, along with political stability and an abundance of high-quality mineral resources, has facilitated Chinese investment in Greenland’s mining sector in recent years. Chinese mining companies now operating in Greenland have, however, faced a number of problems along the way. A dearth of international management skills and stringent social and environmental legislation in particular have proved to be major challenges for Chinese mining companies investing in Greenland